Maternal Eating Behavior and Problematic Eating Behaviors of Children Undergoing Weight Loss Treatment: A Cluster Analysis - Ramalho, Sofia (Child Obes, 2020)
Background: Research on the interplay between mothers' and children's eating behaviors is needed to better inform sensitive and tailored interventions for treatment-seeking children with overweight/obesity. The present study aimed to identify mothers' eating behavior phenotypes, investigating their associations with problematic eating behaviors of children undergoing weight loss treatment in two central hospitals. Methods: This is a cross-sectional study evaluating 136 mother–child dyads (Mothers: age 39.58 ± 5.40 years; Children: n = 75 female; age 10.13 ± 1.37 years). Mothers' eating behavior (restraint, emotional, and uncontrolled eating) and depression/anxiety, and children's problematic eating attitudes/behaviors were assessed. A cluster analysis (K-means) was performed using mothers' eating behavior dimensions. Multivariate Analysis of Covariance investigated differences between clusters on mothers' and children's sociodemographic, anthropometric, psychological, and eating-related variables. Results: Three clusters emerged: The Disordered Eating group (n = 39) of mothers with the highest scores on emotional eating and uncontrolled eating dimensions, the Restraint Eating group (n = 48), including mothers scoring high in cognitive restraint, and the Low Disordered Eating (n = 49) group where mothers scored low in all eating behavior dimensions. Children of mothers in the Disordered Eating cluster had significantly higher emotional overeating relative to children of mothers in the other two clusters. Conclusions: Distinctive eating behavior profiles of mothers, instead of the presence of single eating behaviors, seem to be associated with specific problematic eating behaviors of children undergoing weight loss treatment. Prospective studies are essential to determine whether these profiles can predict differential weight change trajectories in pediatric obesity treatment.